Amplification factor in shear-activated adhesives: effect of elasticity. Issue 40 (24th September 2021) - Kim, Jae-Kang; Varenberg, Michael
Abstract : While the activated and disactivated pull-off forces decrease, the amplification factor, which represents their ratio, increases with the Young's modulus; this suggests that dry adhesive materials should be carefully chosen for the best performance. Abstract : In contrast to common adhesives used in joining, directional adhesives are designed for a dynamic attachment/detachment operation and, hence, their performance is assessed not only in an activated mode but also in a disactivated mode. Consequently, in addition to a peak adhesive strength, a ratio of maximum over minimum attachment force, which can be called a shear-driven amplification factor, is utilized for their characterization. Considering that the peak adhesive response and the amplification factor both depend on the elasticity of the microstructured surface, here we report a combined numerical and experimental study of the effect of the Young's modulus on the attachment properties of flap-shaped contact elements drawn from polyurethane. Our results demonstrate that while the activated and disactivated pull-off forces decrease, the amplification factor increases as the Young's modulus increases. Given that both the activated pull-off force and the amplification factor should be maximized for the best performance, the Young's modulus has to be carefully chosen based on the characteristics of the objects to be manipulated.